Visible light-induced continuous process for photodegradation of chlorpyrifos using g-C3N4/GO/La2O3 photocatalyst from agricultural aquatic waste - Sahima Tabasum; Ajit Sharma; Nandini Dhupar; Upasana Bagri; Souheen Yousuf; Vibha Kumar; Atheesha Singh; Sudheesh K. Shukla (Chemical Physics Impact, 2024)
The widespread use of pesticides and the formation of by-products on the gradual decomposition of these pesticides have led to environmental pollution, which in turn has caused harm to both human and ecosystem health. Pesticides have been found in water bodies worldwide and are a cause of concern. Photocatalytic reactions have received significant attention in the past few decades for the breakdown of pesticides. Different parameters were studied, including the effects of pH, kinetics, dose, and regeneration. The UV–vis spectroscopy results suggest that the g-C3N4/GO/La2O3 nanocomposite is a superior reusable photocatalyst for the degradation of chlorpyrifos (CPF) compared to pure g-C3N4 and GO/ g-C3N4. This is demonstrated by the fact that the g-C3N4/GO/La2O3 nanocomposite outperforms both of these materials. The increased photocatalytic performance may be attributed to a balance between the band gap, morphology, crystalline quality, and surface area, all of which may be slowing down the electron-hole recombination rates. This may be due to the enhanced photocatalytic performance. In addition, the feasible processes were outlined from radical quenching studies, and the results clearly indicate that the presence of more OH radicals plays an essential role in the process of efficient photodegradation using novel g-C3N4/GO/La2O3 nanocomposites.